Проблеми та визначення якості консолідованих даних - Думанський, Нестор; Видойник, Марія (Видавництво Львівської політехніки, 2017)
The analysis of the problems that arise in the process of consolidation of information. The paper formalizes quality characteristics of consolidated data in dataspaces. There is told the notion of usefulness of data from data sources. There is analysed an architecture for a system of quality evaluation of different types of data.
Keywords: консолідована інформація; консолідація; консолідовані дані; інформаційні продукти; якість даних; корисність даних; характеристики якості